PHYLOGENETIC ANALYSIS OF NUCLEOTIDE SEQUENCE OF HIPERVARIABLE FRAGMENT OF VP2 OF INFECTIOUS BURSAL DISEASE VIRUS ISOLATED IN INDONESIA - Kade Mahardika, I Gusti Ngurah; Parede, Lies (Jurnal Veteriner; Vol 9 No 2 (2008))
Nucleotide sequence of hypervariable fragment of VP2 of infectious bursal disease virus (IBDV) isolated in Bali and Indonesia were compared to standard virulent (svIBDV’s) and very virulent (vvIBDV’s) viruses accessed in GeneBank. The comparation were done using the multiple sequence alignment program of Mega 3.1. The sequence were aligned by the ClustalW Method (Mega 3.1), that is grouping the sequences into clusters by examining the distance between all pairs. The sequences were aligned pair wise, then as groups. Phylogenetic tree were constructed using Neighbor-Joining and Bootstrap-tested. The analysis showed that IBDV can be clustered into 2 major groups, i.e. America-Europe and Australia clusters. The America-Europe cluster is further divided into two sub-clusters, i.e. classic IBD and vv-IBD. Classic-IBD is represented by standard STC, Cu-1, Variant A, F52-70, and PBG98 viruses. Two IBDV’s isolated in Bali and the most of other Indonesian isolates belong to sub-cluster vv-IBD and share a common cluster with IBDV that were recently reported as very virulent strains. One exceptional isolate is Indo 13, which is groupped into classic IBD, and closely related to classical American standard virus, STC.
Keywords: nucleotide squence, hypervariable fragment, IBDV